Advancements and controversies in vascular malformation management: A Systematic review. - Singh, Sudhanshu; M.G. Rayee,; S.C.Jha,; Verma, Amitabh; Mandal, Anirudh Prasad (Student's Journal of Health Research Africa, 2025)
Background Congenital vascular malformations encompass a wide spectrum of anomalies, ranging from isolated capillary, venous, lymphatic, and arteriovenous malformations to complex mixed forms. These anomalies may occur as solitary lesions with minimal impact or as part of syndromic conditions, such as Klippel-Trenaunay Syndrome and Parkes-Weber Syndrome, which are associated with significant morbidity due to limb overgrowth and tissue abnormalities. Additionally, the PIK3CA-related overgrowth spectrum (PROS) represents a distinct subset driven by somatic PIK3CA mutations, which complicates diagnosis and management. Objective: This study aims to systematically review the classification, pathogenesis, genetic factors, diagnostic approaches, and treatment modalities for vascular malformations and associated syndromes. Methods In order to perform a systematic review, peer-reviewed publications, clinical recommendations, and expert consensus statements on vascular malformations were found using PubMed, Scopus, Web of Science, and Google Scholar. Studies published within the last two decades were prioritized, with an emphasis on recent advancements. Results Genetic insights have redefined vascular malformation classification, with PIK3CA, TEK (TIE2), and RASA1 mutations playing a crucial role in pathogenesis. Advanced imaging techniques, including MRI and digital subtraction angiography (DSA), remain the gold standard for precise diagnosis, while genetic testing enhances diagnostic accuracy and guides personalized treatment. Conventional therapies such as sclerotherapy and embolization demonstrate 70–85% success rates; however, targeted molecular therapies, including Sirolimus and Alpelisib, have shown superior outcomes in PIK3CA-related cases. Conclusion The evolving landscape of vascular malformation management highlights the shift toward precision medicine, integrating advanced imaging, genetic diagnostics, and molecular-targeted therapies. Recommendations Encouraging international collaborations among researchers, clinicians, and geneticists can accelerate advancements in vascular malformation research. Quality-of-life assessments should be incorporated into research to evaluate the long-term psychological and functional impacts of various treatments.